Dexter in the dark : a novel - Lindsay, Jeffry P. (New York : Doubleday, 2007)
Miami crime scene investigator--and a serial killer dedicated to eliminating evil people--Dexter Morgan confronts his ultimate adversary, a sinister enemy that even terrifies Dexter's inner monster, and must use his sharpest investigative talents to find and destroy his enemy.
"The killer character that inspired the hit Showtime original series Dexter"--Jkt.
Keywords: Forensic scientists -- Fiction; Vigilantes -- Fiction; Serial murderers -- Fiction; Miami (Fla.) -- Fiction; Psychological fiction; Suspense fiction